Analytical performance assessment of a novel active mooring system for load reduction in marine energy converters. (15th September 2016) - Luxmoore, Jamie F.; Grey, Simon; Newsam, David; Johanning, Lars
Abstract: Reliability and storm survival of Marine Energy Converters are critical to their commercial development and deployment. The Intelligent Active Mooring System (IAMS) is a novel device intended to minimise extreme and fatigue loading in mooring lines through a non-linear load–extension curve that is variable in operation to adjust to the prevailing metocean conditions. An analytical model of IAMS, validated by physical model tests at the Dynamic Marine Component test facility at the University of Exeter, is used in a numerical simulation of the performance of IAMS as part of the mooring system of the South West Mooring Test Facility buoy. A 10 m length of IAMS can reduce the rms line tension in normal operating conditions by up to 21% and the peak line tension in storm conditions by up to 21% when compared to braided nylon mooring lines. Peak line tension reductions of over 50% can be achieved if a longer IAMS unit is used. The resulting mooring system can be optimised to give load reductions in a wide range of metocean conditions; while variable pre-tension could be used for tidal range compensation or to ease access for installation and maintenance. Abstract : Highlights: Novel mooring system that can be optimised to suit the metocean conditions. Control of the line stiffness results in significantly reduced peak loads. Peak load reductions of over 50% have been simulated in storm conditions. Variable pre-tension for tidal compensation or access for maintenance.